Lack of cyclin E immunoreactivity in non-malignant breast and association with proliferation in breast cancer. - Scott, K. A. (Nature Publishing Group, 1997)
Cyclin E is a G1 cyclin that is essential for the transition from G1 to S phase in the cell cycle. Alterations to cyclin E expression or regulation could be important in tumorigenesis. Previous immunohistochemical and immunoblotting studies have investigated the expression of cyclin E in breast carcinomas. In this study, cyclin E has been investigated in a range of non-malignant and malignant breast using immunohistochemistry. Normal and benign tissue from pre- and post-menopausal women (39 cases), non-involved tissue from cancer-containing breasts (47 cases), ductal carcinoma in situ (22 cases) and invasive breast carcinomas (109 cases) have been examined. There was no reactivity in any of the non-malignant breast. Only one ductal carcinoma in situ contained more than 5% reactive cells. A total of 28% of invasive carcinomas had > 5% of reactive cells (range 0-88% positive cells, mean 12.59%, median 1.0%). A significant association was found with poorer differentiation (P < 0.001), high MIB1 index (P < 0.001), lack of oestrogen receptor (0.05 > P > 0.025) and the presence of p53 protein (0.05 > P > 0.025). Virtually all cases with cyclin E and p53 were poorly differentiated. The presence of cyclin E is therefore only found in breast malignancies and is associated with more aggressive features, including high proliferation. IMAGES: